Pyla-Vigla: A Case Study Assessing the Imperial Strategies of the Hellenistic Diadochoi in Cyprus - Olson, Brandon R.; Moore, R. Scott; Landvatter, Thomas; Stephens, Justin (Études et Travaux, 2021)
The aim of the present study is to examine the mechanisms the Diadochoi implemented to gain and maintain control over Cyprus using Pyla-Vigla, a recently discovered fortified garrison, as a case study. Alexander the Great’s successors faced a seemingly insurmountable problem: How does one govern, control, and maintain the largest territorial empire the world had ever seen? Alexander’s imperial strategy was predicated upon maintaining native governing institutions of newly subjugated lands and appointing new leaders. This system could not work for the Diadochoi because without a clear path to succession, a twenty-nine-year period of incessant conflict ensued throughout the Eastern Mediterranean. The surviving successors adopted various strategies to exercise imperial authority over their rivals, which ultimately led to the creation of three ruling Hellenistic dynasties: Ptolemies, Seleucids, and Antigonids. Pyla-Vigla represents one of many such strategies.